2002
DOI: 10.1046/j.1365-8711.2002.05233.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of radio plasma in clusters of galaxies

Abstract: We present three-dimensional hydrodynamical simulations of buoyant gas in a typical cluster environment. The hot matter was injected continuously into a small region off-set from the cluster centre. In agreement with previous analytic estimates we found that the bubbles evolve very differently depending on their luminosity. Using tracer particles we computed radio maps of the bubbles based on different assumptions about the magnetic field. In the radio band the bubbles closely resemble FRI sources. For the bub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 46 publications
5
74
1
Order By: Relevance
“…Theoretical and numerical models to interpret these observations have also been developed by e.g. Churazov et al (2001) and Brüggen et al (2002).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical and numerical models to interpret these observations have also been developed by e.g. Churazov et al (2001) and Brüggen et al (2002).…”
Section: Introductionmentioning
confidence: 99%
“…A substantial number of bubbles have been observed in a number of clusters as depressions in the X-ray surface brightness, sometimes associated with a low level of remnant radio emission (Heinz et al, 1998;McNamara et al, 2001). Moreover, it has been shown that a lot of energy in the form of bubbles may reside in clusters as the bubbles are difficult to detect (Brüggen et al, 2002). The buoyant rise and the subsequent mixing of high-entropy gas with the cluster material can lead to a significant re-structuring of the inner regions of a cooling flow.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we performed highly resolved two-dimensional hydrodynamic simulations of buoyant gas in a typical cluster environment similar to previous simulations of lower resolution (Brüggen et al, 2002;Quilis et al, 2001). These simulations were performed using the FLASH code (Fryxell et al, 2000), which uses an explicit piece-wise parabolic method to solve the equations of compressible hydrodynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Malyshkin (2001); Narayan & Medvedev (2001); Voigt et al (2002); Ruszkowski & Begelman (2002); Cho et al (2003); Soker et al (2004); Voigt & Fabian (2004); Soker (2004); Jubelgas et al (2004); Chandran & Maron (2004); Dolag et al (2004) 6 Churazov et al (2001); ; Quilis et al (2001); Brüggen et al (2002); Chandran (2004); Hoeft & Brüggen (2004); Dennis & Chandran (2005). There have been also observations of hot gas bubbles (Mazzotta et al 2004), which may also contribute to the cool core heating in a very similar way as the radio bubbles (Soker & Pizzolato 2005) …”
Section: Magnetic £Elds In Cool Coresmentioning
confidence: 97%